Analysis of calls to the Mobile First-Aid Medical Services in a Brazilian capital city - Marilene Nonnemacher Luchtemberg; Denise Elvira Pires de Pires; Soraia Dornelles Schoeller; Fabricio Pagani Possamai (Universidade Federal do Ceará, 2015)
It is a documentary study to characterize Mobile First-Aid Medical Services calls that did not provide assistance in the state of Santa Catarina, SC, Brazil from 2007 to 2010. Data were collected from assistance reports, being noticed 393,912 prank phone calls to the institution. The main reason for the assistance not being provided was the removal of the victim by third parties. The others were refusal of care, the removal of the patient and incorrect address. There were significant differences (p<0.05) between the years under study concerning the calls received by the Mobile First-Aid Medical Services and the number of prank phone calls received in the state macro-regions. The results indicate the need of investment in health education activities, reducing costs and increasing effectiveness. It is also necessary to improve communication between Mobile First-Aid Medical Services and the other services (Military Police and Fire Brigade) reducing the number of assistance.